Identifikasi dan Pengendalian Potensi Bahaya di Tempat Kerja (Studi Kasus: Perusahaan XYZ) - Doa, Yakobus; Kusuma, Maritha Nilam (Environmental Engineering Journal ITATS, 2024)
Company XYZ is an industry that produces packaging and boxes with a capacity of 32 billion sheets per year. This company uses a lot of chemicals in its production process, which can be a source of hazards. In addition, several machines used in the production process can cause many health and work safety risks. This research aimed to identify and control potential hazards in the workplace by implementing a descriptive method. It investigated the problems through observations, interviews, and literature studies. The results of this study indicated that the production process stage got a risk rating score of 12, classified as a high-risk level. Meanwhile, all of them were classified as medium, with a risk assessment below 12. This company must control high-risk activities by taking immediate actions to reduce the risks until they can be controlled strictly and precisely. It must also conduct workforce development activities in the workplace, beginning with OHS training programs, emergency procedures emergency training, nd rehearsals to increase the company's productivity.